Migrants and cluster internationalization: case studies of Antwerp and Tel Aviv - Henn, Sebastian; Schäfer, Susann (The globalization of regional clusters, 2021)
While cluster research for a long time has analyzed the internal networks that characterize regional clusters, more recent work aims at understanding how clusters connect to geographically distant regions. In this context, it was argued that external cluster linkages facilitate access to knowledge and practices about technologies and foreign markets across geographical distances, thereby enabling clustered firms to successfully adapt to changing environments and preventing the entire setting from detrimental lock-ins. Even though an increasing number of studies have dealt with the role of intra- or inter-organizational ties for knowledge transfers, their role for corporate internationalization is far from being systematically explored. In particular, the role of migrants in establishing and maintaining such network relations has been neglected. Based on two case studies, the Antwerp diamond cluster and the Israeli IT cluster, our paper seeks to address this research gap by elaborating on different mechanisms that migrants have on internationalization at both the firm and the cluster level.
Gesehen am 29.01.2025
Keywords: Aufsatz im Buch